WESTERN CONIFER SEED BUG (LEPTOGLOSSUS OCCIDENTALIS H.) – A THREAT TO CONIFER PLANTATIONS IN UKRAINE - Stiurko, M. (Bulletin of Lviv National Environmental University. Series Agronomy, 2025)
Coniferous plants play a vital role in park and forest plantations, both in our country and around the world. However, the areas dedicated to these plants are decreasing each year. They face numerous environmental threats and human activities, such as deforestation, destruction of parks and reserves, and the impact of pests and diseases, all of which diminish their quality. Harmful insects are among the biggest threats to both natural and artificial plantings, as their mass reproduction can lead to significant damage to the flora. Invasive insect species, in particular, pose a serious risk due to their adaptability, rapid reproduction, and ability to invade new territories, which can harm existing plant species. One such invasive pest is the western conifer seed bug (Leptoglossus occidentalis), which was introduced to Eurasia from the Americas. Unfortunately, it is not listed as a harmful organism in Ukraine's quarantine regulations concerning plant health. This pest is atypical for coniferous vegetation in our region, yet it has managed to establish itself across the entire country due to its remarkable adaptability. The western conifer seed bug feeds on more than 40 species of coniferous plants, targeting young and mature cones and causing complete or partial destruction of seeds. Access to high-quality, viable seeds is crucial for establishing young plantations and ensuring the ability of forests to self-renew. A shortage of healthy seedlings can negatively impact the ecological functions of forest and park areas. The aim of our research was to document the presence of the western conifer seed bug in Lviv region and to determine the number of productive generations it has each year. We found that the pest has expanded its habitat and feeding range into the western Forest Steppe of Ukraine, and it had not been previously recorded in Lviv region. Currently, studies on the characteristics and impacts of the western conifer seed bug are insufficient, and there are no established recommendations for measures to prevent its mass proliferation. Therefore, the challenge of protecting and preserving productive coniferous tree plantations remains unresolved.